The influence of price on purchase decision with quality of service as intervening variable - Eka Mayastika Sinaga (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Changes to systems such as transactions and marketing are all driven by progress towards a more contemporary period. Along with the increasing and growing industrial world, competition in the business world is very tight. Industry players are increasingly facing the challenge of gaining the market share they want. This study uses quantitative research methods and aims to determine the effect of price changes on purchasing decisions, with service quality as an intervening variable. A case study at the XL AXIATA product distributor outlet PT. Cross Archipelago Access, Tebing Tinggi City. The results of the study can be concluded as follows in the first hypothesis, the price variable (X) has a positive and significant effect on service quality (Z); the second hypothesis is accepted, meaning that the price (X) has no significant effect on purchasing decisions (Y); and the third hypothesis is accepted, meaning that service quality (Z) has a positive and significant effect on purchasing decisions (Y). Path analysis shows that the direct effect of variable X on variable Y is 0.163. The indirect effect through the Z variable is 0.2114. Based on the calculation results, the direct effect on Y is greater than the indirect effect through Z.